Characterization and Genomic Analyses of Pseudomonas aeruginosa Podovirus TC6: Establishment of Genus Pa11virus - Tang, Chaofei; Deng, Chuanjiang; Zhang, Yi; Xiao, Cong; Wang, Jing; Rao, Xiancai; Hu, Fuquan; Lu, Shuguang (Frontiers in Microbiology, 2018)
Phages have attracted a renewed interest as alternative to chemical antibiotics. Although the number of phages is 10-fold higher than that of bacteria, the number of genomically characterized phages is far less than that of bacteria. In this study, phage TC6, a novel lytic virus of Pseudomonas aeruginosa, was isolated and characterized. TC6 consists of an icosahedral head with a diameter of approximately 54 nm and a short tail with a length of about 17 nm, which are characteristics of the family Podoviridae. TC6 can lyse 86 out of 233 clinically isolated P. aeruginosa strains, thus showing application potentials for phage therapy. The linear double-stranded genomic DNA of TC6 consisted of 49796 base pairs and was predicted to contain 71 protein-coding genes. A total of 11 TC6 structural proteins were identified by mass spectrometry. Comparative analysis revealed that the P. aeruginosa phages TC6, O4, PA11, and IME180 shared high similarity at DNA sequence and proteome levels, among which PA11 was the first phage discovered and published. Meanwhile, these phages contain 54 core genes and have very close phylogenetic relationships, which distinguish them from other known phage genera. We therefore proposed that these four phages can be classified as Pa11virus, comprising a new phage genus of Podoviridae that infects Pseudomonas spp. The results of this work promoted our understanding of phage biology, classification, and diversity.